Long‐term 4‐year safety of saxagliptin in drug‐naive and metformin‐treated patients with Type 2 diabetes. Issue 12 (19th July 2013) - Rosenstock, J.; Gross, J. L.; Aguilar‐Salinas, C.; Hissa, M.; Berglind, N.; Ravichandran, S.; Fleming, D.
Abstract Aims To evaluate the safety of saxagliptin ± metformin over 4 years in patients with Type 2 diabetes mellitus. Methods Drug‐naive (n = 401; study 11) or metformin‐treated (n = 743; study 14) adults with HbA1c of 53–86 mmol/mol (7.0–10%) were enrolled in two randomized, placebo‐controlled, double‐blind trials of saxagliptin 2.5, 5 or 10 mg/day. Patients rescued during or completing 24 weeks of treatment could continue in a 42‐month long‐term blinded phase, for which the primary goal was assessment of safety and tolerability. Between‐group efficacy was not evaluated in the long‐term phase of study 11. Time to rescue or discontinuation because of inadequate glycaemic control, change from baseline in HbA1c and percentages of patients achieving HbA1c < 53 mmol/mol (< 7.0%) were assessed in study 14. Results No new safety findings were noted during the long‐term phase. Most adverse events were mild or moderate, with slightly greater frequency of upper respiratory infections with saxagliptin. Hypoglycaemic event rates were similar with saxagliptin and placebo. In study 14, time to rescue or discontinuation because of inadequate glycaemic control was longer with saxagliptin plus metformin than for placebo plus metformin. From baseline to week 154, HbA1c decreased with saxagliptin but increased with placebo. Conclusion Saxagliptin monotherapy or add‐on to metformin is generally safe and well tolerated, with no increased risk of hypoglycaemia, for up to 4 years.